Economic assessment of real-time biofouling monitoring using SpectroMarine in a 100,000 m3/day SWRO plant in the gulf region - Mahmoud, Amr Mohamed; AlGhamdi, Ahmed S.; Ahmed, Sultan (Frontiers in Membrane Science and Technology, 2026)
Biofouling is a significant operational challenge in seawater reverse osmosis (SWRO) desalination, particularly in biologically active environments like the Arabian Gulf. This study assesses the operational and economic impacts of implementing SpectroMarine, an autonomous real-time monitoring system, in a 100,000 m3/day SWRO facility. SpectroMarine leverages in-situ fluorescence and UV-visible absorbance measurements to detect early-stage biological activity in feedwater, enabling predictive maintenance and proactive fouling control. An economic model was constructed using literature-based operational baselines, including membrane lifespan, cleaning frequency, specific energy consumption, chemical dosing, and downtime. Implementation of SpectroMarine is projected to reduce energy consumption by 3%, cleaning-in-place (CIP) frequency by 50%, membrane replacement costs by 20%, and pretreatment chemical usage by 25%. Furthermore, unplanned downtime may be reduced by up to 50%. The model estimates annual savings of approximately 2.89 million SAR, with a payback period of less than 2 months under Gulf-specific operating conditions. The presented results are based on a literature-derived economic model incorporating sensitivity analysis, and no site-specific field validation has been conducted at this stage.